5-Fluorouracil rechallenge after 5-fluorouracil-induced hyperammonemic encephalopathy. Issue 3 (March 2019) - Boilève, Alice; Wicker, Camille; Verret, Benjamin; Leroy, Florence; Malka, David; Jozwiak, Mathieu; Pontoizeau, Clément; Ottolenghi, Chris; De Lonlay, Pascale; Ducreux, Michel; Hollebecque, Antoine
Abstract : For several decades, 5-Fluorouracil (5-FU) has been the backbone of many chemotherapy regimens for various tumor types. Its most common side effects are gastrointestinal disorders, mucositis, myelosuppression, hand–foot syndrome, and rarely cardiac toxicity. More rarely, 5-FU infusion can induce hyperammonemic encephalopathy. 5-FU toxicities can be worsened by complete or partial genetic and/or phenotypic dihydropyrimidine dehydrogenase deficiency. Here, we report the case of a patient who initially developed a 5-FU-induced hyperammonemic encephalopathy after receiving FOLFIRINOX (oxaliplatin, irinotecan, folinic acid, and 5-FU) chemotherapy with bevacizumab to treat a metastatic gastrointestinal cancer of unknown primary. Thereafter, the patient was rechallenged successfully by the same chemotherapy regimen (FOLFIRINOX) for more than 6 months with a protocol consisting in a free protein diet, and administration of ammonium chelators, and Krebs and urea cycle intermediates, to prevent further hyperammonemia. We also present a review of the literature on 5-FU rechallenge after 5-FU-induced hyperammonemic encephalopathy.